Analisis Komparasi Kinerja Keuangan Sebelum dan Sesudah Pemboikotan Produk Israel - Romario Dominico Hartono (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze differences in financial performance before and after the boycott of products associated with Israel among nine companies listed on the Indonesia Stock Exchange (IDX). The study employs a quantitative approach with a descriptive-comparative method, using secondary data obtained from companies’ financial statements for the periods before and after the boycott. The results indicate that liquidity and profitability ratios declined after the boycott, reflecting a weakened ability of companies to meet short-term obligations and a decrease in profit levels caused by declining sales and increased operational pressure, while solvency ratios remained relatively stable, although several companies showed increased reliance on debt. The study concludes that social pressure in the form of a boycott has a tangible impact on the financial performance of public companies in Indonesia, particularly in terms of liquidity and profitability; therefore, it is recommended that companies strengthen risk management strategies and maintain a sound capital structure to mitigate the effects of similar social pressures in the future.